P181 Indwelling pleural catheters for malignant pleural effusions – do septations change outcomes?. (12th November 2015) - Nuttall, E; Balata, H; Al-Aloul, M; Evison, M; Holme, J
Abstract : Introduction: The insertion of indwelling pleural catheters (IPCs) allows outpatient based management of pleural effusions and has been shown to be effective as a primary management strategy and following failed attempts at pleurodesis. The presence of septations may be associated with incomplete drainage and may make the procedure more complex. This study aimed to assess if the presence of septations on thoracic ultrasound changed the outcome of IPC insertion and to review complication rates. Method: Prospective data is collected for patients undergoing insertion of IPCs at a tertiary pleural referral centre. Pre-procedure thoracic ultrasound is performed in all patients and a grading of septations made; no septations, mild (<4), moderate (4–9), severe septations (>9). Immediate, early (30 days) complications as well as six month follow-up data are recorded. This study is a retrospective analysis of this prospectively maintained database. Results: A total of 47 patients with complete datasets were identified between 2013–2014; 34% (16/47) had mild/moderate/severe septations (n = 7, 5, 4 respectively) and 66% (31/47) had no septations. There was no significant difference in the number of patients achieving resolution of pleural effusion and pleurodesis whereby the IPC could be removed according to the presence of septations (pleurodesis in those with no septations 16%, 5/31 vs. 13%, 2/16 in those with septations, p = 1.0). There were no patients in either group in whom the drain was removed due lack of drainage in the context of a persistent pleural collection. There was no significant difference in overall complication rate according to the presence of septations (16%, 5/31, in the no septation group vs 13%, 2/16, in the septation group, p = 1.0). Conclusion: These results suggest that the presence of septations on the pre-insertion thoracic ultrasound do not affect the rate of pleurodesis or drain removal due to lack of drainage and persistent pleural effusion. The numbers in the study are small and a limitation is the lack of assessment of post-procedure breathlessness in our patients (e.g. with a visual analogue scale). The presence of septations should not deter consideration of IPC insertion in the management of malignant pleural effusions.